Efficacy of adjuvant metronidazole therapy on peri-implantitis: a systematic review and meta-analysis of randomized clinical studies - López-Valverde, Nansi; López-Valverde, Antonio; Blanco-Rueda, José Antonio (Frontiers in Cellular and Infection Microbiology, 2023)
Peri-implant diseases are pathological conditions that affect the survival of dental implants. Etiological studies are limited, accepting a prevalence of 20% at implant level and 24% at patient level. The benefits of adjuvant metronidazole are controversial. A systematic review and meta-analysis of RCTs according to PRISMA and PICOS was performed with an electronic search in the last 10 years in MEDLINE (PubMed), WOS, Embase and Cochrane Library. Risk of bias was measured using the Cochrane Risk of Bias Tool and methodological quality using the Jadad scale. Meta-analysis was performed with RevMan, Version 5.4.1, based on mean difference and standard deviation, with 95% confidence intervals; the random-effects model was selected; the threshold for statistical significance was defined as p < 0.05. Thirty-eight studies were collected and 5 were selected. Finally, one of the studies was eliminated because of unanalyzable results. All the studies reached a high methodological quality. A total of 289 patients were studied with follow-up periods from 2 weeks to 1 year. Statistical significance was only found, with respect to the use of adjunctive metronidazole, in the pooled analysis of the studies (p=0.02) and in the analysis of the radiographic values reported on peri-implant marginal bone levels, in the studies with 3-month follow-up (p=0.03). Discrepancies in the use of systemic metronidazole require long-term randomized clinical trials (RCTs) to determine the role of antibiotics in the treatment of peri-implantitis.